2010
DOI: 10.1097/bot.0b013e3181cf0404
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of the Upper and Second Sacral Segment Safe Zones in Normal and Dysmorphic Sacra

Abstract: Sacral dysmorphism occurred in 44% of patients in this consecutive series. Many anatomic differences were consistently found between the two morphologies with clinical relevance to iliosacral screw placement. Specifically, the dysmorphic upper sacral segment safe zone is significantly smaller and more obliquely oriented but is still large enough to accommodate an iliosacral screw in nearly all patients. The second sacral segment safe zone is approximately transversely oriented in both sacral types but is more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
191
4
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 159 publications
(214 citation statements)
references
References 28 publications
11
191
4
1
Order By: Relevance
“…A compensatory larger transsacral osseous S2 corridor in dysmorphic versus nondysmorphic sacra [7,8,11], was confirmed in our study, as shown by a weak negative correlation of the S1 and S2 transsacral corridor diameters. Furthermore, the larger range of maximum corridor diameters for S1 compared with the smaller more-sigmoidal distribution for S2 (Fig.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…A compensatory larger transsacral osseous S2 corridor in dysmorphic versus nondysmorphic sacra [7,8,11], was confirmed in our study, as shown by a weak negative correlation of the S1 and S2 transsacral corridor diameters. Furthermore, the larger range of maximum corridor diameters for S1 compared with the smaller more-sigmoidal distribution for S2 (Fig.…”
Section: Discussionsupporting
confidence: 87%
“…4). Using the largest 10-mm diameter cutoff, as reported by Gardner et al [8] and Moed and Geer [24], transsacral osseous corridors at the S1 and S2 vertebrae would have been too narrow in 36% and 26% of pelves compared with 32% and 12% when using the 9-mm cutoff. Measured cylindrical diameters in our study (S1, 13 ± 0.3 mm; S2, 12 ± 2 mm) are similar to those reported by Lee et al [19] (S1: 14 ± 4 mm; S2 11 ± 3 mm) and larger than those reported by Vanderschot et al [37].…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations